Desain Dan Implementasi Video Codec Berbasis H.265 Dan Video Enkripsi Pada Autonomous Underwater Robot - Faidhon Nur; Agung Nugroho Jati; Unang Sunarya (eProceedings of Engineering, 2015)
Abstract— UNEXAR is a mini autonomous underwater robot in a cubic shape similar to a drone. This robot can be used to monitor local environment and observe an object below much more closely than otherwise needing us to wear underwater suit which is bothersome. It can also be used as an exploration device, to map unreachable area somewhere that’s not in our line of sight. Robot can also be used to find an object with specific color using camera and image processing in debian based operating system. Other than that as an AUV it is able to carry some load and transport it somewhere near as long as the power is sufficient. AUV Design compromised by planting artificial intelligence, planning the mechanical structure and electronics design. Component primarily discussed are locomotion mechanism, particle density and buoyancy. Experiment data, measurement data, failures and lesson learned from the research are also included. Index Terms— Buoyancy, Engineering, Locomotion, Mechanical, Monitor, Particle density, Robot.